A model for classifying breast masses in ultrasound images - Shereen Ekhlas Morsy; Neveen Mahmoud Abd-Elsalam; Zaid Abdu Al-Saidy; Ahmed Hesham Kandil; Ahmed Mohammed El-Bialy; Abou-Bakr Mohammed Youssef (Institute of Advanced Engineering and Science, 2024)
The most frequent type of cancer among women is breast cancer. Artificial intelligence (AI) researchers are developing automated systems to assist in the detection and classification of breast cancer. This study explores machine learning (ML) and deep learning (DL) as two AI methods for identifying benign and malignant breast tumors in ultrasound images. The investigation assesses the performance of various computer-aided detection and diagnosis (CAD) systems, which utilize either handcrafted features or deep features extracted from DL models. Furthermore, three models for CAD deep learning-based systems were implemented using convolutional neural networks (CNN), convolutional autoencoders (CAE), and deep features with CNN models, and compared with three traditional ML models based on handcrafted (texture) features. The results indicate that the deep features of the CNN model are promising, achieving a mean accuracy of 95% with a standard deviation of 1.1%.